Resistance of bamboo scrimber against white-rot and brown-rot fungi. Issue 1 (2nd January 2020) - Kumar, Anuj; Ryparovà, Pavla; Kasal, Bohumil; Adamopoulos, Stergios; Hajek, Petr
ABSTRACT: Bamboo scrimber is one of the most emerging structural materials for future building applications and it possesses properties comparable to other natural wood-based engineered materials such as glulam, laminated veneer lumber and cross-laminated timber. The goal of this work was to study the decay resistance of bamboo scrimber against white-rot ( Trametes versicolor ) and brown-rot fungi ( Serpula lacrymans ). Bamboo scrimber samples were incubated in petri dishes with the wood-decaying fungi and the weight loss after 12 weeks was measured. The surface morphology of fungal-degraded bamboo scrimber was evaluated using optical microscopy. Based on the percentage weight loss, bamboo scrimber could be classified as highly resistant against bio-deterioration by white and brown-rot fungi.